Imunomarcação de células CD3+ e CD79a+ nas lesões descamativas e ulcerativas de cães com leishmaniose - Torres Neto, Rafael [UNESP]; Pinto Rodrigues, Marcela Marcondes [UNESP]; Amorim, Renée Laufer [UNESP]; Conceicao, Lissandro Goncalves; Luvizotto, Maria Cecília Rui [UNESP]; Verde Silva Franco, Sonia Regina [UNESP] (Universidade Estadual de Londrina (UEL), 2008)
Canine visceral leishmaniasis is an endemic infectious disease in some regions from São Paulo state and even though it is a systemic disease, in the dog, the main clinical sign is dermatological. Thirty dogs with positive results in serology (IFI) and parasitological exams (fine needle aspiration) for leishmaniasis from Aracatuba city were evaluated. They only showed dermatological signs and were divided in two groups, one with exfoliative (n=15) and other with ulcerative (n=15) lesions. There was significant statistical difference between CD3 and CD79a population in the same dermatological pattern, and with CD79a population between exfoliative and ulcerative patterns (p<0,05).
Expression of CD3 and CD79a cell markers in exfoliative and ulcerative skin lesions in dogs with leishmaniasis
Keywords: exfoliative dermatitis; ulcerative dermatitis; leishmaniasis; immunohistochemistry; dog